2008
DOI: 10.1007/s12043-008-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

110°C thermoluminescence glow peak of quartz — A brief review

Abstract: The 110 • C glow peak of quartz, though unstable at room temperature, has worked wonderfully in archaeology and retrospective dosimetry due to its pre-dose sensitization property. Various aspects of the peak, like its nature, defect centres involved, the impact of different stimuli and its application have been extensively studied. The main aims of this review are to (i) summarize briefly the work carried out on the various facets of this TL glow peak during the last four decades and (ii) identify the areas wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…Franklin et al (1995), have shown the presence of at least four of the quartz's TL peaks, namely at 95-110, 150-180, 200-220 as well as 305-325°C, depending on the heating rate. Similar results were also reported by other authors, such as Ogundare et al (2006), Koul (2008) and Preusser et al (2009). Additional glow peaks are also available in the literature for different quartz samples as well as different detection optics, such as at 250-270°C as well as the one at 350-375°C (Wintle, 1997;Thomsen, 2004).…”
Section: Introductionsupporting
confidence: 87%
“…Franklin et al (1995), have shown the presence of at least four of the quartz's TL peaks, namely at 95-110, 150-180, 200-220 as well as 305-325°C, depending on the heating rate. Similar results were also reported by other authors, such as Ogundare et al (2006), Koul (2008) and Preusser et al (2009). Additional glow peaks are also available in the literature for different quartz samples as well as different detection optics, such as at 250-270°C as well as the one at 350-375°C (Wintle, 1997;Thomsen, 2004).…”
Section: Introductionsupporting
confidence: 87%
“…Quartz of different origins have associated glow peaks ranging from 95-110, 150-180, 200-220 as well as 305-325°C, depending on the heating rate used. Similar results, but not exact, are also available in the literature for different quartz samples as well as different detection optics [17,21,28,34,36]. The influence of excitation dose and thermal treatment on the TL properties of glow peaks in quartz is widely studied [17,21,24].…”
Section: Introductionsupporting
confidence: 53%
“…Similar results, but not exact, are also available in the literature for different quartz samples as well as different detection optics [17,21,28,34,36]. The influence of excitation dose and thermal treatment on the TL properties of glow peaks in quartz is widely studied [17,21,24]. Studies of TL characteristics of quartz [20], CaF2:Dy [37], muscovite mica [33] among other materials have shown glow curves having overlapping peaks.…”
Section: Introductionmentioning
confidence: 61%
“…It must be recognized here that the prime cause for the pre-dose phenomenon is the accumulation of the charge in the R-centres in nature (Koul 2008). The firing episode removes all the holes from these centres in the case of ceramics.…”
Section: Discussionmentioning
confidence: 98%